2011
DOI: 10.1186/1745-6215-12-125
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of complex interventions in clinical trials: development of a taxonomy to classify and describe fall-prevention interventions

Abstract: BackgroundInterventions for preventing falls in older people often involve several components, multidisciplinary teams, and implementation in a variety of settings. We have developed a classification system (taxonomy) to describe interventions used to prevent falls in older people, with the aim of improving the design and reporting of clinical trials of fall-prevention interventions, and synthesis of evidence from these trials.MethodsThirty three international experts in falls prevention and health services re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 71 publications
0
145
0
9
Order By: Relevance
“…A better understanding of these factors and their effect on the implementation process is necessary. Effective fall prevention must consist of multifactorial interventions that target each resident's fall risk profile, and should be tailored to address context-specific barriers and put into action the identified facilitators Grimshaw et al, 2012;Lamb et al, 2011;Vlaeyen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A better understanding of these factors and their effect on the implementation process is necessary. Effective fall prevention must consist of multifactorial interventions that target each resident's fall risk profile, and should be tailored to address context-specific barriers and put into action the identified facilitators Grimshaw et al, 2012;Lamb et al, 2011;Vlaeyen et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The trial’s results will be reported using domains and categories described in the taxonomy developed by the Prevention of Falls Network Europe, to allow future synthesis of evidence, or study replication [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Falls are common in older populations and levels of frailty, increasing age, impairment of functional status (cognitive/physiological), reduced mobility and environmental factors increase risk 1. Identification and reduction of modifiable risk factors is a key to falls prevention.…”
Section: Contextmentioning
confidence: 99%